The case for cultural genocide: the formulation of a working definition - Tavaras, Tye (AUC Knowledge Fountain, 2011)
The Genocide Convention is hailed as a great protection mechanism and the one document that will prevent future destruction of groups. This convention however, has a variety of shortcomings that fail to protect groups outside of attempted physical destruction. An article criminalizing cultural genocide is a devastating omission and this paper seeks to create a working legal definition to be used a framework for creating an article or convention to provide such criminalization. Beginning with an analysis of the drafting of the Genocide Convention with particular attention paid to the importance of culture in the foundation of the convention as well as the debate surrounding the inclusion of cultural genocide in the final draft. The arguments used to prevent the inclusion of cultural genocide into the final draft provide insight into the fears of states and also provided the foundation of the argument for the necessity of the criminalization of cultural genocide. The second section analyzes the intersection of culture, law, and genocide. Defining culture as an abstraction is difficult and has to be broken down into components of culture, which can provide clear legal standards for cultural rights protection and the criminalization of cultural genocide. An analysis of current cultural protection mechanisms provides an understanding of the dominant viewpoint of culture in the international community. Furthermore, this viewpoint provided a majority accepted definition of cultural components requiring protection that was used to frame a definition of cultural genocide. The final section explicates the necessity of a definition of cultural genocide. The remnants of cultural genocide in the Genocide Convention seen in the prohibition of the forced transfer of children, demonstrates the importance of preventing loses of culture. Furthermore, the definition of cultural genocide is framed by the existing definition of genocide, and uses the combination actus reus and dolus specialis in its determination. Similar to genocide, the final definition of cultural genocide requires the intent to destroy a group as the distinguishing factor between genocidal acts and human rights violations.